Plasma simulation of hot-surface-microwave hybrid ion sources. (1st June 2022) - Zhang, A.L.; Peng, S.X.; Wu, W.B.; Ma, T.H.; Cui, B.J.; Jiang, Y.X.; Li, K.; Zhang, J.F.; Zhang, T.; Wen, J.M.; Xu, Y.; Guo, Z.Y.; et al.
Abstract: To generate high-current hard-to-ionize elements such as B +, a hybrid ion source that combines electron cyclotron resonance and thermal surface ionization, which is called a high-temperature surface microwave source (HSMS), is under development. A high-temperature hot surface (2000°) and microwave heating are the essential components of an HSMS to produce high-energy electrons for B + generation. A helical tungsten filament is used in the HSMS source to obtain a high temperature and provide an axial configuration with a magnetic field of approximately 87.5 mT for the 2.45 GHz electron cyclotron resonance (ECR). The effects of high-temperature surface ionization and ECR ionization were separately evaluated. The magnetic field configuration, microwave power, and air pressure have been studied through this plasma model. A 30% B + improvement was achieved.